PENGARUH MEDIA SOSIAL DAN DAYA TARIK WISATA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DOMESTIK DI PANTAI MELASTI, BALI - Ni Komang Krisnayani; Hanugerah Kristiono Liestiandre; I Gusti Putu Ade Pranjaya (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
The emergence of various kinds of social media has an impact on the industrial revolution in the tourism sector, marked by the ease of accessing information through social media. The tourism transformation of the 4.0 era changes the entire cycle of the tourism ecosystem, especially in terms of the dissemination and consumption of information on social media related to travel activities. The purpose of this research is to see the impact of media social and tourist attraction on the domestic tourist visit-decision in Melasti Beach, Badung. This research was designed using quantitative methods with multiple linear regression analysis. Using qualitative and quantitative data, with total sample of 250 respondents from domestic tourists visiting Melasti Beach. Sampling was done by distributing 30 questionnaires to visitors at Melasti Beach. The analysis technique was tested using the classical assumption test. Most of the respondents came from Jakarta, most of whom were women. The results of this study indicate that there is an influence between social media and tourist attraction on the decision to visit domestic tourists classified as positive.